Answer:
D
Step-by-step explanation:
For a function in the form f(x) = x, we can say:
- the function f(x) = ax is a vertical stretch if a>1 and compress if 0<a<1
- the function -f(x) is the original, flipped over x-axis
<em>keeping the 2 rules in mind, we can say that</em>
<em>vertical stretch by a factor of 3 would make it f(x) = 3x</em>
<em>Then</em>
<em>flip over x-axis would make it f(x) = -3x</em>
<em />
answer choice D is right
Answer:
AB = 8.857 cm
Step-by-step explanation:
Here, we are given a <em>right angle</em>
in which we have the following things:
![\angle A = 90 ^\circ\\\angle C = 41 ^\circ\\\text{Side }BC = 13.5 cm](https://tex.z-dn.net/?f=%5Cangle%20A%20%3D%2090%20%5E%5Ccirc%5C%5C%5Cangle%20C%20%3D%2041%20%5E%5Ccirc%5C%5C%5Ctext%7BSide%20%7DBC%20%3D%2013.5%20cm)
Side <em>BC </em>is the hypotenuse here.
We have to find the side <em>AB</em>.
Trigonometric functions can be helpful to find the value of Side AB here.
Calculating
:
Sum of all the angles in
is
.
![\Rightarrow \angle A + \angle B + \angle C = 180^\circ\\\Rightarrow 90^\circ + \angle B + 41^\circ = 180^\circ\\\Rightarrow \angle B = 49^\circ](https://tex.z-dn.net/?f=%5CRightarrow%20%5Cangle%20A%20%2B%20%5Cangle%20B%20%2B%20%5Cangle%20C%20%3D%20180%5E%5Ccirc%5C%5C%5CRightarrow%2090%5E%5Ccirc%20%2B%20%5Cangle%20B%20%2B%2041%5E%5Ccirc%20%3D%20180%5E%5Ccirc%5C%5C%5CRightarrow%20%5Cangle%20B%20%3D%2049%5E%5Ccirc)
We know that <em>cosine </em>of an angle is:
![cos \theta = \dfrac{\text{Base}}{\text{Hypotenuse}}\\\Rightarrow cos B = \dfrac{AB}{BC}\\\Rightarrow cos 49^\circ = \dfrac{AB}{13.5}\\\Rightarrow AB = 13.5 \times 0.656\\\Rightarrow AB = 8.857 cm](https://tex.z-dn.net/?f=cos%20%5Ctheta%20%3D%20%5Cdfrac%7B%5Ctext%7BBase%7D%7D%7B%5Ctext%7BHypotenuse%7D%7D%5C%5C%5CRightarrow%20cos%20B%20%3D%20%5Cdfrac%7BAB%7D%7BBC%7D%5C%5C%5CRightarrow%20cos%2049%5E%5Ccirc%20%3D%20%5Cdfrac%7BAB%7D%7B13.5%7D%5C%5C%5CRightarrow%20AB%20%3D%2013.5%20%5Ctimes%200.656%5C%5C%5CRightarrow%20AB%20%3D%208.857%20cm)
So, side AB = 8.857 cm
.
Answer: The value of x is = 5.
Step-by-step explanation:
So we are given the equation:
3x + 7 = 22
We just have to isolate 3x and move 7 to the other side:
3x = 22 -7
3x = 15
Now divide:
x = 15/3
x = 5
There you go!
Answer:
x= -5
Step-by-step explanation:
Divide each term by
5
and simplify.
Answer:
yes
Step-by-step explanation: